Oppositinines A and B: New vasorelaxant beta-carboline alkaloids from neisosperma oppositifolia - Ahmad, K.; Thomas, N.F.; Hadi, A.H.A.; Mukhtar, M.R.; Mohamad, K.; Nafiah, M.A.; Takeya, K.; Morita, H.; Litaudon, M.; Arai, H.; Awang, Khalijah (Pharmaceutical Soc Japan, 2010)
A phytochemical study on the bark of Neisosperma oppositifolia (Apocynaceae) yielded two new beta-carboline indole alkaloids, oppositinines A (1) and B (2), together with five known alkaloids, isoreserpiline, isocarapanaubine, vobasine, 10-methoxydihydrocorynantheol-N-oxide, and ochropposinine oxindole. Structural elucidation of 1 and 2 was performed using 21) NMR methods. Oppositinines A (1) and B (2) showed potent vasorelaxant effects on the rat aorta.